Purification and Characterization of Acetyl-Coenzyme A Carboxylase from Diclofop-Resistant and -Susceptible Lolium multiflorum. - Evenson, K. J. (1994)
Acetyl-coenzyme A carboxylase (ACCase) was purified >100-fold (specific activity 3.5 units mg-1) from leaf tissue of diclofopresistant and -susceptible biotypes of Lolium multiflorum. As determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, the purified fractions from both biotypes contained a single 206-kD biotinylated polypeptide. The molecular mass of the native enzyme from both biotypes was approximately 520 kD. In some cases the native dimer from both biotypes dissociated during gel filtration to form a subunit of approximately 224 kD. The inclusion of 5% (w/v) polyethylene glycol 3350 (PEG) in the elution buffer prevented this dissociation. Steady-state substrate kinetics were analyzed in both the presence and absence of 5% PEG. For ACCase from both biotypes, addition of PEG increased the velocity 22% and decreased the apparent Km values for acetyl-coenzyme A (acetyl-CoA), but increased the Km values for bicarbonate and ATP. In the presence of PEG, the Km values for bicarbonate and ATP were approximately 35% higher for the enzyme from the susceptible biotype compared with the resistant enzyme. In the absence of PEG, no differences in apparent Km values were observed for the enzymes from the two biotypes. Inhibition constants (Ki app) were determined for CoA, malonyl-CoA, and diclofop. CoA was an S-hyperbolic (slope replots)-I-hyperbolic (intercept replots) noncompetitive inhibitor with respect to acetyl-CoA, with Ki app values of 711 and 795 [mu]M for enzymes from the resistant and susceptible biotypes, respectively. Malonyl-CoA competitively inhibited both enzymes (versus acetyl-CoA) with Ki app values of 140 and 104 [mu]M for ACCase from resistant and susceptible biotypes, respectively. Diclofop was a linear noncompetitive inhibitor of ACCase from the susceptible biotype and a nonlinear, or S-hyperbolic-I-hyperbolic, noncompetitive inhibitor of ACCase from the resistant biotype. For ACCase from the susceptible biotype the slope (Kis) and intercept (Kii) inhibition constants for diclofop versus acetyl-CoA were 0.08 and 0.44 [mu]M, respectively. ACCase from the resistant biotype had a Ki app value of 6.5 [mu]M. At a subsaturating acetyl-CoA concentration of 50 [mu]M, the Hill coefficients for diclofop binding were 0.61 and 1.2 for ACCase from the resistant and susceptible biotypes, respectively. The Hill coefficients for diclofop binding and the inhibitor replots suggest that the resistant form of ACCase exhibits negative cooperativity in binding diclofop. However, the possibility that the nonlinear inhibition of ACCase activity by diclofop in the enzyme fraction isolated from the resistant biotype is due to the presence of both resistant and susceptible forms of ACCase cannot be excluded.